An Endometrioid Ovary Cyst and Fallopian Tube in the Inguinal Canal: Conservative or Surgical Management? - Sema Ovalı; Ahmet Yılmaz; Gürkan Zorlu (Medical Network, 2016)
The presence of an ovary in the inguinal canal, presenting as an inguinal hernia is an extremely rare condition in premenaposal women. We present a case, which was managed expectantly before but needed surgery thereafter. A 31 year old woman who had 2 cesarean sections before presented with a painful and red mass in the left inguinal canal. Absence of the left ovary had been noted during previous cesarean sections and she had two attacks of pelvic inflammatory disease. She could not get pregnant through natural route and ovulation induction treatment was initiated upon which a left inguinal mass appeared. A previous attempt to aspirate the mass had been unsuccessful. Ultrasonographic diagnosis was hemorrhagic ovary cyst and abcess. Laparoscopic right salpingectomy was performed due to right hydrosalphyx and left inguinal hemorrhagic mass was excised surgically. Pathological examination confirmed that the mass was an ovary. Most of the cases of hernia containing ovary and other genital organs are found in children, but they may be seen in premenaposal or menaposal women also. Some of them are diagnosed before the operation but most of them are diagnosed during or after the operation. Asymptomatic cases may be managed expectantly but in symptomatic patients, surgical removal is indicated.